Assimetria de transmissão de preços na cadeia produtiva da sojicultura: 2011 a 2017 - Presotto, Elen (2017)
The soybean complex is very important in Brazilian exports, and in 2016 represented 14% of the total exported by the country. This representativeness is a reflection of the attractiveness of soybeans in the international market and the productive capacity of Brazil. In this way, the expansion in production is the result of internal capacities (great expansion of land) and acquired (investments in research and development of new technologies). It should be noted that, as a commodity, soy has its price formation in the international market. With this, it is expected that there will be price transmission between markets, since it is assumed that the soybean producer is a price taker, due to the nature of the market structure in which it operates. For example, the occurrence of market failures, such as the presence of market power and the costs of adjustments, are some explanations for the presence of Asymmetry Price Transmission (APT). The type of ATP will depend on the expectation that agents establish relative to their competitors. From this, when there are positive or negative shocks in the price paid to the soybean producer, one can reflect on the existence of different intensities in these transmission channels, there is an occurrence of rigidity in the reduction of prices. When the price of soybeans falls, not necessarily the wholesale and the retail reflect the price shocks in the same intensity and direction, characterizing the presence of APT in the markets studied. In this context, this study aims to investigate the process of spatial price transmission between the international market and the Brazilian and vertical soybean producer of the different levels of wholesale/retail market for the price paid to the soy producer, the market is taken Paraná as unit of analysis. The methodology used was panel data for spatial analysis and the Error Correction Model (ECM) for vertical. The results point to the presence of cointegration and long-term equilibrium between the markets studied. The estimated econometric models were efficient in representing the price transmission scenario, since all presented the presence of asymmetry of transmission of prices. Also, the presence of contemporary impact symmetry in the space market analysis was verified. With regard to vertical markets, it was possible to perceive that they can respond in different ways to the existence of market power, so that it is possible to verify both positive and negative asymmetries. Finally, it can be seen that in both markets, since the producer depends on an inefficient market structure, it absorbs the negative shocks (reduction in prices) with greater intensity than the positive ones (increases in prices). This fact generates distortions in the price formation process in the soybean complex, and the most benefited links of the complex are the processing and exporting companies.